Comparison of two low‐hazard organic solvents as individual and cosolvents for the fabrication of polysulfone membranes. Issue 1 (2nd October 2019) - Dong, Xiaobo; Shannon, Halle D.; Parker, Caleb; De Jesus, Samantha; Escobar, Isabel C.
Abstract: Petroleum‐derived solvents commonly used in membrane fabrication are often hazardous and toxic, so the investigation of safer alternatives is important. In this study, two low‐hazard solvents, methyl 5‐(dimethylamino)‐2‐methyl‐5‐oxopentanoate (Rhodiasolv® PolarClean) and gamma‐valerolactone (GVL), were investigated as sole solvents and as cosolvents to cast polysulfone membranes via nonsolvent induced phase inversion. Normalized viscosity was introduced as an indicator of dope solution homogeneity and was used to compare the required time of mixing to achieve full dissolution of the polymer in the different solvents/solvent mixtures. All dope solutions made with low‐hazard solvents were found to be more viscous than those made with traditional solvents, which meant additional mixing time was needed, and that fabricated membranes were morphologically different. With respect to operation, membranes cast from dope solutions containing equal amounts of PolarClean and GVL displayed the most similar flux curves and solute rejection to those made using the traditional solvent tested.